Perilaku Impulsive Buying Pengguna Shopee Paylater Pada Mahasiswa Fisip Universitas Riau - Yola Yuliana Putri; Risdayati Risdayati (Jurnal Ilmiah Wahana Pendidikan, 2026)
This study aims to examine the impulsive consumption behavior of students who use paylater services and the correlation between Paylater and students' impulsive behavior, using Jean Baudrillard's consumerism theory. This study uses a qualitative approach, by conducting in-depth interviews with students from the Faculty of Social and Political Sciences, University of Riau, who actively use paylater services for their shopping activities. The results show that students' impulsive consumption behavior is more influenced by signal factors, such as the pursuit of social status and the formation of group identity, rather than considering the functional needs of goods. Consumption is not only interpreted as fulfilling needs, but also as a means of representing self-image and following emerging trends on social media. The role of social media, especially TikTok and Instagram, as well as various promotions offered through Paylater, Paylater not only functions as a payment tool, but also influences students' consumption patterns, where the intensity of use is correlated with increased impulsive buying behavior, especially among students who are still in the stage of learning financial management and self-control. Sociologically. This study concludes that impulsive consumption behavior among college students is influenced not only by economic factors but also by social dynamics and sign values, which are further reinforced by the existence of pay-later services, a tool that facilitates impulse purchases. These findings underscore the importance of improving financial literacy among college students to manage consumption behavior more wisely and responsibly.